Logistics cost structure for farmer of durain in Chanthaburi province - Thoucharee, Sanan; Junwiang, Waraporn (Asia-Pacific Journal of Science and Technology, 2017)
This research has applied the Activity Based Costing study’s logistics cost structure for farmer of durian in chanthaburi province. The purpose is to suggest the solution to reduce the logistics cost. The result shows that the farmer’s logistics cost is 4.588 baht/kg. The highest value of logistics costs is quantity cost 2.223 baht/kg. which comes from mostly harvesting. The second highest values is 1.302 baht/kg. of transportation costs which come from deprecia-tion in transportation. The third highest values is 0.930 baht/kg. of inventory costs which is the opportunity cost of storage using in maintains them. So farmers should manage as follows. Firstly the farmers should share labor. Secondly the farmers should share durian transport together. Thirdly the farmers should not stock productivity factors such as fertilizer in large volume because it will expense a lot of money and reduce electricity cost and labor. These Solutions will lead to reduce the logistics costs for farmer of durian in Chanthaburi province.